2016
DOI: 10.2217/epi-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

SLC6A4 Promoter Region Methylation and Socio-Emotional Stress Response in Very Preterm and Full-Term Infants

Abstract: The present study extends previous reports, suggesting that altered SLC6A4 methylation associates with greater socio-emotional stress sensitivity in 3-month-old VPT infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 50 publications
5
50
0
Order By: Relevance
“…12 Additionally, controlling for neonatal and clinical confounders, increased SLC6A4 methylation was found to be predictive of behavioural development and emotional regulation in preterm infants at three months corrected age. 6,13 These findings suggest that gene-specific epigenetic regulation might play a key role in mediating the effect of early NICU pain-related stress exposure on preterm infants' outcomes in emotion regulation. Nonetheless, longitudinal data on emotional regulation in children born preterm are lacking.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…12 Additionally, controlling for neonatal and clinical confounders, increased SLC6A4 methylation was found to be predictive of behavioural development and emotional regulation in preterm infants at three months corrected age. 6,13 These findings suggest that gene-specific epigenetic regulation might play a key role in mediating the effect of early NICU pain-related stress exposure on preterm infants' outcomes in emotion regulation. Nonetheless, longitudinal data on emotional regulation in children born preterm are lacking.…”
Section: Introductionmentioning
confidence: 93%
“…3 NICU life-saving procedures still entail invasive and painful stimulations, such as skin-breaking procedures, and NICU-related stress has been associated with emotional and neuroendocrine disruptions later in life. [4][5][6][7] Emotional dysregulation during early childhood is one of the most reported detrimental outcomes of preterm birth and it is sensitive to early exposure to NICU-related stress and pain. 8,9 The serotonin system is a key regulator of emotional development and stress regulation 10 and the SLC6A4 gene encoding for the serotonin transporter is known to be sensitive to epigenetic regulation through changes in DNA methylation in response to environmental exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The study of emotion self-regulation with preterm infants has been performed by several authors (Montirosso et al, 2016;Muller-Nix et al, 2004). Fuertes, Lopes dos Santos, Beegly, and Tronick (2009) conducted a study with 57 preterm infants observed at three months of life in the FFSF, distinguishing three groups according to the emotion regulation patterns demonstrated over the three episodes: Group 1 with socially positive pattern, Group 2 with socially negative pattern, and Group 3 which pattern of state self-regulation was characterized by self-comforting behavior compared to the other two groups.…”
Section: Palavras-chavementioning
confidence: 99%
“…Past research has suggested that infants’ socio‐emotional regulation should be particularly apparent in conditions that elicit stress, such as maternal unavailability during the Face‐to‐Face Still‐Face (FFSF) paradigm (Mesman, van IJzendoorn, & Bakermans‐Kranenburg, ; Provenzi, Giusti, & Montirosso, ; Tronick, Als, Adamson, Wise, & Brazelton, ). The FFSF is an interactive procedure in which socio‐emotional stress is elicited by the experimental manipulation of maternal availability to interact (i.e., mothers are instructed not to interact with the infant for 2 min, maintaining a still face and eye contact with the infant, namely the Still‐Face episode).…”
Section: Developmental Care For Very Preterm Infants and Their Mothersmentioning
confidence: 99%